Eddy-driven sea-level rise near the frontal region off the east coast of the Korean peninsula during 1993–2020 - Lee, KyungJae; Park, Jae-Hyoung; Park, Young-Gyu (Frontiers in Marine Science, 2024)
Introduction Understanding the underlying dynamics of regional sea-level rise (SLR), which often deviates from global trends, is crucial for mitigating and adapting to the impacts of severe climate change. This study investigated the causes of high regional SLR rates (> 6.0 mm yr-1) around the frontal region near Ulleung Island in the southwestern East/Japan Sea (EJS). Despite exhibiting rates higher than the global average (3.1 mm yr-1) from 1993 to 2020, the reasons for these higher rates in this region have not been clearly elucidated. Methods We aimed to clarify the quantitative effect of the long-term variations of the Ulleung Warm Eddy (UWE) on the high SLR rates near Ulleung Island based on satellite altimetry and ship-based hydrographic data. Results During this period, the temperature within the UWE increased, particularly at the temperature-homogeneous layer of approximately 200 m, the lower boundary of the UWE deepened, and the eddy duration per year increased, resulting in high SLR rates within the eddy owing to the steric height rise. The long-term variations in the internal temperature and vertical thickness of the UWE had significantly comparable impacts on SLR rates, with the duration being less influential. The SLR rates by integrating all long-term variations in the UWE (7.6 mm yr-1) quantitatively explained the high long-term SLR rates at Ulleung Island (7.0 mm yr-1). Discussion The increasing temperature within the UWE was attributed to the rising temperature of water flowing through the southwestern strait (Korean Strait) in late fall, and the deepening lower boundary and the increasing duration of the UWE resulted from the increased horizontal temperature gradients near the front, leading to enhanced baroclinic instability in the subsurface layers. Our findings suggest that long-term variations in mesoscale eddies can significantly influence the regional SLR rates, deviating substantially from the global average in the frontal region.